Book Notes [31, Spring 1993] - Palmer, Bryan D.; Kealey, Gregory S. (Labour/Le Travail, 1993)
The article briefly reviews "Love A Solidarity: A Pictorial History of the NDP, by Cameron Smith, "Industrial Relations in Canadian Industry," edited by Richard P. Chaykowski and Anil Verma, "Reaction and Reform: The Politics of the Conservative Party under R. B. Bennett, 1927-1938," by Larry A. Glassford, "The Un-Canadians: True Stories of the Blacklist Era," by Len Scher, "History of Canadian Youth and Childhood: A Bibliography," by Neil Sutherland, Jean Barman and Linda L. Hale, "The Little Slaves of the Harp: Italian Child Street Musicians in Nineteenth-Century Paris, London, and New York," by John E. Zucchi, "In the Floating Army: F.C. Mills on Itinerant Life in California, 1914, by Gregory R. Woirol, "Visions of a New Industrial Order: Social Science and Labor Theory in America's Progressive Era," by Clarence E. Wunderlin, Jr., "The Lost World of the Craft Printer," by Maggie Holtzberg-Call, "The Trucker's World: Risk, Safety, and Mobility," by J. Peter Rothe, "Avoiding the Cracks: A Guide to the Workers ' Compensation System," by Anne Tramposh, "Feminism and the Women's Movement: Dynamics of Change in Social Movement Ideology and Activism," by Barbara Ryan, "Ethnic Minorities and Industrial Change in Europe and North America," edited by Malcolm Cross, "English and French Towns in Feudal Society: A Comparative Approach," by R.H. Hilton, "The Education of Desire: Marxists and the Writing of History," by Harvey J. Kaye, "White, Male and Middle Class: Explorations in Feminism and History," by Catherine Hall, "William Cobbett and Rural Popular Culture," by Ian Dyck, "European Labour Politics from 1900 to the Depression," by Dick Geary, "Women of the Praia: Work and Lives in a Portuguese Coastal Community," by Sally Cole, "New Trends in Employment Practices: An International Survey," by Walter Galenson, "Strikes Have Followed Me All My Life: A South African Autobiography," by Emma Mashinini, "Status Influences in Third World Labor Markets: Caste, Gender, and Custom," edited by James G. Scoville, ,"Labor and Economic Growth in Five Asian Countries," by Walter Galenson / reviews by Bryan D. Palmer – "The Labor Process and Control of Labor: The Changing Nature of Work Relations in the Late Twentieth Century," edited by Berch Berberoglu, "Culture and the Labour Movement: Essays in New Zealand Labour History," edited by John E. Martin and Kerry Taylor / reviews by Gregory S. Kealey.